2022
DOI: 10.3390/biomedicines10123236
|View full text |Cite
|
Sign up to set email alerts
|

TIGIT Expression on Intratumoral Lymphocytes Correlates with Improved Prognosis in Oral Squamous Cell Carcinoma

Abstract: (1) Background: T-cell immunoglobulin and ITIM domain (TIGIT) is a potential immunotherapeutic target in a variety of malignant entities, and antibody-based treatments are currently under investigation in clinical trials. While promising results were observed in patients with lung cancer, the role of TIGIT in oral squamous cell carcinoma (OSCC) as a biomarker as well as a therapeutic target remains elusive. Therefore, we evaluated the role of TIGIT as a prognostic factor in OSCC. (2) Methods: Here, we describe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Indeed, the PD-1/PD-L1 axis is not the only relevant mechanism of immune evasion. Other molecules, such as TIGIT and FOXP3, have been investigated as regulatory key points of the TME and, therefore, as potential targets of new immunotherapeutic drugs [ 52 , 53 ], and so-called tertiary lymphoid structures, as shown to be important in prediction of the outcome in HNSCC [ 54 ]. Moreover, the presence of HPV-related carcinogenesis and differences in oral cavity microbiota have been shown to influence the composition of the TME and the interactions among cells [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the PD-1/PD-L1 axis is not the only relevant mechanism of immune evasion. Other molecules, such as TIGIT and FOXP3, have been investigated as regulatory key points of the TME and, therefore, as potential targets of new immunotherapeutic drugs [ 52 , 53 ], and so-called tertiary lymphoid structures, as shown to be important in prediction of the outcome in HNSCC [ 54 ]. Moreover, the presence of HPV-related carcinogenesis and differences in oral cavity microbiota have been shown to influence the composition of the TME and the interactions among cells [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, results are conflicting, and several studies have failed to prove a prognostic role for TIGIT expression, specifically in esophageal cancer [46], medullary thyroid carcinoma [47], NSCLC [34,48,49], and SCLC [50]. In contrast, other authors have reported a positive prognostic impact of TIGIT-enriched TME on survival, as seen in oral squamous cell carcinoma [51], breast cancer [52], and melanoma [39]. Further studies are needed to deepen our knowledge of TIGIT expression, both in the neoplastic microenvironment and in tumor cells, and its substantial correlation with the PD1/PD-L1 axis, particularly in the field of lung cancer, on which most immunotherapy trials are focused.…”
Section: Tigit As An Immunohistochemical Biomarker: Current Knowledgementioning
confidence: 99%
“…For instance, Food and Drug Administration (FDA) granted approval for the use of Pembrolizumab, a humanized anti-programmed death receptor 1 (PD-1) antibody for the treatment of some patients with an advanced form of head and neck cancer in 2016 (6) whereas cetuximab, a monoclonal antibody that binds competitively to the EGFR, was approved by the FDA for late-stage (metastatic) and resistant cases of squamous cell carcinoma (SCC) of the head and neck in 2011 (7). Apart from PD-1, other immune checkpoints such as cytotoxic T-lymphocyte protein 4 (CTLA4), T-cell immunoreceptor with Ig and ITIM domains (TIGIT), and lymphocyte activation gene 3 protein (LAG3) are considered new rational therapeutic targets (8,9). In addition, oncolytic viruses (OVs), antigenic vaccines, adoptive T cell transfer (ACT), costimulatory agonists therapy, are also under development (10).…”
mentioning
confidence: 99%